THE EFFECT OF DIFFERENTIATED LEARNING ON EFL ACHIEVEMENT: A META-ANALYSIS - Shalsa Aledya Putri; Mujiono Mujiono; Teguh Sulistyo (Premise: Journal of English Education and Applied Linguistics, 2025)
The present meta-analysis explored the effects of differentiated learning on EFL learners' achievements, examining the impact of various moderating factorsâ€¤ The study synthesized eight experimental studies (2014–2025), adhering to PRISMA guidelines, and found that differentiated Instruction had a large, statistically significant effect on English achievement (Hedges' g = 1â€¤92)â€¤ Overall effect sizes were evaluated, and moderator analyses were applied to assess variation by educational level, language-learning target, and geographical regionâ€¤ The study revealed that learners at the primary level demonstrated greater gains in English achievement than their secondary-level peers, suggesting age-related responsiveness to differentiated instructionâ€¤ The study showed that those who learned reading and writing skills improved more than those who learned general English language learningâ€¤ The findings indicate that differentiated learning can be aligned with learners' needs and characteristics to make the teaching–learning procedure more personalized and interactiveâ€¤ This study, therefore, favors more research into finding how best differentiated learning can be implemented in different educational domainsâ€¤